2021
DOI: 10.1111/brv.12690
|View full text |Cite
|
Sign up to set email alerts
|

A farewell to arms and legs: a review of limb reduction in squamates

Abstract: Elongated snake-like bodies associated with limb reduction have evolved multiple times throughout vertebrate history. Limb-reduced squamates (lizards and snakes) account for the vast majority of these morphological transformations, and thus have great potential for revealing macroevolutionary transitions and modes of body-shape transformation. Here we present a comprehensive review on limb reduction, in which we examine and discuss research on these dramatic morphological transitions. Historically, there have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 104 publications
0
36
0
Order By: Relevance
“…Variation in phalangeal counts and digit morphology can arise from adaptive evolution to new ecological niches including aquatic, fossorial, scansorial, and cursorial habits, but also disruptions to limb development (Romer, 1956;Shapiro et al, 2007). In Anthracodromeus, a lack of any common aquatic or fossorial anatomical specializations makes these lifestyles unlikely candidates for explaining the hypophalangy observed in the manus and pes (Gans, 1975;Greer, 1987;Greer, 1991;Fedak and Hall, 2004;Camaiti et al, 2021). We find the most likely explanation for the combination of features found in the manus and pes of Anthracodromeus is that they are adaptations for scansoriality.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Variation in phalangeal counts and digit morphology can arise from adaptive evolution to new ecological niches including aquatic, fossorial, scansorial, and cursorial habits, but also disruptions to limb development (Romer, 1956;Shapiro et al, 2007). In Anthracodromeus, a lack of any common aquatic or fossorial anatomical specializations makes these lifestyles unlikely candidates for explaining the hypophalangy observed in the manus and pes (Gans, 1975;Greer, 1987;Greer, 1991;Fedak and Hall, 2004;Camaiti et al, 2021). We find the most likely explanation for the combination of features found in the manus and pes of Anthracodromeus is that they are adaptations for scansoriality.…”
Section: Discussionmentioning
confidence: 65%
“…We find the most likely explanation for the combination of features found in the manus and pes of Anthracodromeus is that they are adaptations for scansoriality. Unlike living fossorial lizards (Camaiti et al, 2021), the reduced phalangeal counts of Anthracodromeus contrast the proportional elongation of phalanges in the manus and pes, which accounts for their formidable length. Hypophalangy in Anthracodromeus reduced the number of joints in the affected fingers and toes and consequently likely reduced the flexibility of the elongated digits, which may have provided further stability while clinging to surfaces and climbing over terrain.…”
Section: Discussionmentioning
confidence: 83%
“…Limbless species were coded as character state 1, limb‐reduced ones as 2, and fully limbed species as 3. All models considered treated limb status as an ordered character, as to become limbless a species must necessarily first become limb‐reduced (Bergmann & Morinaga, 2019; Brandley et al, 2008; Camaiti et al, 2021).…”
Section: Results and Examples Of Data Usagementioning
confidence: 99%
“…We used these criteria rather than loss of digits because a significant proportion of taxa with four ‘long’ limbs are characterised by digit loss (e.g. Carlia, and outside of lizards, Equus ), while some short‐limbed elongated taxa (e.g., Anepischetosia ) are characterised by no digit losses at all (Camaiti et al, 2021; Greer, 1991). We chose the arbitrary cut‐offs of 15% (for forelimbs) and 20% (for hindlimbs) of SVL as we observed that virtually all species characterised by losses of digital elements and/or increased presacral vertebrae counts fall within those bounds.…”
Section: Methodsmentioning
confidence: 99%
“…The family is also morphologically and ecologically diverse, occurring in a range of habitats on every continent apart from Antarctica. Whereas the typical skink has four well-developed limbs, limb reduction and loss are common, with numerous independent events of limb reduction estimated in the group [ 34 , 35 ], including multiple times within some genera [ 36 , 37 ]. Limb reduction is typically correlated with a fossorial lifestyle and accompanied by a suite of other adaptations [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%